Anti-Diabetic Drug Utilization in Fasa, Southern Iran: A Pharmacoepidemiological Study Based on PERSIAN Cohort Data - Leila Zarei; Seyyed Taghi Heydari; Farzad Doostishoar; Azizallah Dehghan; Reza Tabrizi (International Journal of Nutrition Sciences)
Background: In order to design better management for anti-diabetic medication, pharmacoepidemiological studies are required to have an update on the drug utilization. Therefore, the present study was performed with the aim of pharmacoepidemiological analysis on utilization of antidiabetic drugs based on PERSIAN cohort data.Methods: In this study, 10138 participants were included by baseline data. Use of anti-diabetic medications based on Anatomical Therapeutic Chemical (ATC) code A10 was provided. Quantitative and qualitative variables were illustrated using mean±standard deviation (SD) and frequency (percent). Logistic regression was employed to define associated factors with categorical outcomes.Results: The descriptive analysis showed that 12.3% (n=1249) of the participants had diabetes, while only 5.3% (n=540) of them had utilized anti-diabetic medications. Totally, 94.7% of the participants did not take any anti-diabetic drug, 3% received monotherapy and 2% reported a combination of anti-diabetic medication therapies. Also, the higher ages showed a more chance for use of anti-diabetic medications (40-59 years: OR=3.72, 95% CI: 2.38-5.81; ≥60, OR=5.61, 95% CI: 3.41-9.22).In addition, married and employed participants were more likely to take anti-diabetic medications. Also, having cardiovascular diseases (CVDs), fatty liver and pregnancy were associated with a higher significant chance of using anti-diabetic medications.Conclusion: Less than half of the patients diagnosed with diabetes received anti-diabetic drugs indicating the importance of medication adherence training programs in this group of patients.